Occupational accidents among healthcare workers in a tertiary health facility in Enugu state, South-East Nigeria - Nwoga, Hope O.; Ajuba, Miriam O.; Nwankwo, Malachy M. (International Journal Of Community Medicine And Public Health, 2020)
Background: The risk of acquiring blood borne infections by healthcare workers (HCWs) in developing countries is accentuated by the high prevalence of blood borne infections, poor provision of personal protective equipment (PPEs), negative socio-cultural factors and poorly maintained healthcare systems. The objective was to determine the prevalence of occupational accidents among HCWs in a tertiary health facility in Enugu state, South-East Nigeria. Methods: A descriptive cross-sectional study that used mixed method technique. The quantitative data was collected using a self-administered questionnaire while an in-depth interview (IDI) guide was used for the qualitative data. Manual content analysis was done for the qualitative data while the quantitative data was analysed using SPSS version 22. The significance level placed at p<0.05. Results: The prevalence of mucous membranes exposure to blood/body fluids were the same in the past 6 and 12 months (22.0%) while the mean number of exposures were 3.93±3.002 and 4.47±4.008 respectively. The prevalence of needle stick or sharps injury in the past 6 and 12 months were 17.0% and 23.0% while the mean numbers of injuries were 2.24±2.001 and 2.48±2.858 respectively. The injuries occurred majorly while recapping needles and breaking injection ampoules. Emergent themes from the IDI were also recapping of needles and breaking of injection ampoules. Conclusions: There is still high prevalence of occupational accidents among the studied HCWs training and re-training of HCWs on the dangers associated with these occupational accidents.